Development Module Based Search, Solve Create and Share (SSCS) to Train Critical Thinking Ability in Body Defense System Material - Wulan, Tari Anjar; Antika, Rindi Novitri (Journal of Biology Education, 2021)
This research and development aiment to: 1) find out the module development products based on the SSCS model to train critical thinking skills in body defense system material, 2) find out the feasibility of developing module based on the SSCS model to train critical thinking skills in body defens system material. The research and development were carried out using procedures according to Borg and Gall (2003) which were limited to the 7 th stage of the ten stages. Data analysis techniques used qualitative descriptive analysis technique and quantitative analysis. The result of the research and development showed that 1) module product based on the SSCS model were developed based on facione’s critical thinking ability thinking aspects (2015) which visualized the objectives, material, activities and evalution questions. 2) module feasibility viewed from the result of validation including material expert validation got an average of 75,4 % with good quality, media experts got an average of 68,8% with good quality, evaluation experts got a men of 74,4 % with good quality, linguistists and readability got q mean of 78,37 % with good quality, validation of Biology education practitioners got an average of 96,5 % with very good qualfications and validation of students with an average of 84,7 % got very good qualifications. Based on the overall percentage it could be conclude that the module was feasible to use